Iliopsoas tendonitis after hip arthroscopy: prevalence, risk factors and treatment algorithm - Adib, Farshad (J Hip Preserv Surg, 2018)
The incidence of iliopsoas tendonitis (IPT) has not previously reported following hip arthroscopy for femoroacetabular impingement with or without labral tears. (i) What is the incidence of IPT following hip arthroscopy; (ii) are there any demographic risk factors and (iii) are there any operative techniques that are risk for IPT? Retrospective study. Hip arthroscopy patients from 2005 to 2012 were included. Patients were diagnosed via physical examination findings and were excluded if they had pre-operative IPT. Records were reviewed for demographics, operative reports and operative procedures. All patients received either labral debridement, labral repair, osteoplasty or a combination of those procedures. A standardized rehabilitation protocol was used. Of 252 patients, 60 (24%) had IPT. Twenty-eight (47%) had symptom resolution with activity modification, physical therapy and NSAIDs. Thirty-two (53%) required corticosteroid injection at a mean of 25 weeks after surgery. Seven (12%) required revision arthroscopy and iliopsoas release to resolve the symptoms. There were no patient-specific risk factors, differences based on surgical technique, and number of portals did not matter. Patients should minimize exercises that activate the iliopsoas after hip arthroscopy. The cause of IPT could be related to unaddressed abnormal mechanics, tendon scarring or improper physical therapy. Further studies are needed to investigate the reasons for this, as well as specific techniques to lower its incidence. The incidence of IPT after hip arthroscopy has an incidence of 24%. Additionally, we provide readers with a rehabilitation protocol to minimize this complication. WHAT IS KNOWN ABOUT THE SUBJECT: This subject has not previously been described. WHAT THIS STUDY ADDS TO EXISTING KNOWLEDGE: We are the first to report IPT after hip arthroscopy.